Transformasi Tata Kelola Filantropi Islam Urban: Studi Kasus Model Pemberdayaan Sosioekonomi Holistik Masjid Raya Bintaro Jaya - Rizqiyah Rizqiyah; Titiek Titiek; Erma Fatmawati; Wahyu Wibowo (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study examines the paradigm shift of contemporary Islamic philanthropy in Indonesia from traditional charity toward a systematic economic empowerment model aligned with Maqashid al-Sharia, particularly the protection of wealth (hifz al-mal). It aims to analyze the governance transformation at Masjid Raya Bintaro Jaya and to explore how the integration of trustworthiness (amanah) and professional ethics converts ZISWAF (zakat, infaq, sadaqah, and waqf) funds into instruments for competitive community economic self-reliance in a heterogeneous urban context. Employing a holistic case study design with a qualitative–interpretive approach, the research captures the institutional dynamics and governance practices in depth. The findings propose an integrative “Urban Islamic Philanthropy” model in which the mosque functions not only as a ritual space but also as a hub for socio-economic empowerment supported by modern accountability mechanisms and digital-based transparency. These results offer a practical roadmap for mosque managers (takmir) to optimize the socio-economic potential of the ummah through credible and sustainable governance.